2012
DOI: 10.3390/ijms131114203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Superfine Grinding on Antidiabetic Activity of Bitter Melon Powder

Abstract: The antidiabetic activities of bitter melon powders produced with lyophilization/superfine grinding and hot air drying/normal grinding were investigated in vivo for selecting a suitable bitter melon processing procedure. After a five-week treatment, bitter melon lyophilized superfine grinding powder (BLSP) had a higher antidiabetic activity with reducing fasting blood glucose levels from 21.40 to 12.54 mmol/L, the serum insulin levels from 40.93 to 30.74 mIU/L, and restoring activities of SOD compared with tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 53 publications
(65 reference statements)
2
33
1
Order By: Relevance
“…4A) because the surface area for reaction with water and the content of the component for dissolution in water were both increased at smaller particle sizes. These results were in agreement with a report of Zhu et al (27) in which grinding of bitter melon power increased the water solubility index. The decrease in particle size of bitter melon resulted in an increase in levels of water soluble sugars and proteins.…”
Section: Resultssupporting
confidence: 95%
See 1 more Smart Citation
“…4A) because the surface area for reaction with water and the content of the component for dissolution in water were both increased at smaller particle sizes. These results were in agreement with a report of Zhu et al (27) in which grinding of bitter melon power increased the water solubility index. The decrease in particle size of bitter melon resulted in an increase in levels of water soluble sugars and proteins.…”
Section: Resultssupporting
confidence: 95%
“…5B). Zhu et al (27) suggested that grinding improves the extraction efficiency for nutritional components Non-grinding group, 12 mesh; Group 1 (coarse), 12 mesh or greater; Group 2 (moderate), 12-40 mesh; Group 3 (fine), 40 mesh and smaller 2) All values are presented as a mean±SD. Values with different letters indicate significant differences among groups at p<0.05 based on a oneway ANOVA.…”
Section: Resultsmentioning
confidence: 99%
“…This technology plays an important role in application of DF (Zhao et al, 2009). Compared with other samples ground with traditional mechanical methods, superfine powder bears good physical properties like lowering the interfacial tension and effect of steric hindrance (Zhu et al, 2012;Ting et al, 2014). To date, the superfine grinding technology has also been applied in biotechnology (Wu et al, 2012) and foodstuffs, such as ginger powder (Zhao et al, 2009), Astragalus membranaceus powder (Zhao et al, 2010), wheat bran DF and wine grape pomace DF (Zhu et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Various extracts of MC are studied for biological activities, including anti-oxidant [15] , anti-diabetic [16] , anti-cancer [17] , anti-inflammatory [18] , anti-bacterial [19] , antifungal [20] , anti-viral [21] , anti-HIV [22] , anti-helminthic [23] , anti-mycobac-terial [24] , hypotensive [25] , anti-obesity [26] , immunomodulatory [27] , anti-hyperlipidemic [28] , hepatoprotective [29] , and neuropro-tective [30] activities. Several chemical constituents such as cucurbitane type triterpenoids, cucurbitane type glycosides, triterpene saponins, phenolic, and flavonoid compounds, and some protein fractions have been isolated from MC [31] .…”
Section: Introductionmentioning
confidence: 99%